"Anytime, anyplace, anywhere"—A sample selection model of mobile internet adoption in german agriculture. Issue 2 (15th February 2020) - Michels, Marius; Fecke, Wilm; Feil, Jan‐Henning; Musshoff, Oliver; Lülfs‐Baden, Frederike; Krone, Saskia
Abstract: Mobile internet is considered one of the most important developments in information and communication technology due to its considerable effect on both the economy and our daily lives. Furthermore, mobile internet is an essential tool for overcoming the rural–urban digital divide. With respect to agriculture, mobile internet can play a central role in information gathering as well as the implementation of precision and smart farming technologies. Yet, no study has identified the determinants of mobile internet adoption in agriculture. Using a bivariate probit model with a sample selection and a representative data set from 815 German farmers, this study showed that, among other characteristics, the age of the farmer, farm size and location, as well as familiarity with internet risks is associated with mobile internet adoption in agriculture. These results may be of interest to policy makers, who deal with internet infrastructure, and providers of farm equipment that rely on mobile internet connection. [EconLit citations: Q16].